El derecho de identidad, no inmediato del nacido vivo, afecta sus derechos fundamentales. - Franco Morante, Felipe Javier (2015)
The research project has as its theme "The law of identity, not immediately of live birth, affects their fundamental rights" in the city of Quevedo, Los Rios Province during 2014. The investigation of this issue is because it is necessary to identify children immediately after birth, because it is a social phenomenon that has been going on all the time, undermining the existence of children as citizens , violating their rights and produce legal effects on them. It is structured by chapter in a total of six. The first chapter is called THE PROBLEM, develops: The contextualization of Macro, Meso, Micro analysis, making regarding the origin of the problem with a National, Provincial and institutional landscape respectively, critical analysis, problem formulation, questions of research, delimitation of the object of research, justification, the general and specific objectives. The second chapter called THEORETICAL, where emphasizes a systematic study of the Right to Identity of live birth enshrined in the Ecuadorian legislation, international conventions and treaties, from a doctrinal and legal historical approach. In the third chapter called METHODOLOGY, develops: modalities of research, type of research, population and sample collection plan information through the use of surveys to lawyers in free practice and…………..